A Lead‐Free and High‐Energy Density Ceramic for Energy Storage Applications. Issue 9 (19th August 2013) - Correia, Tatiana M.; McMillen, Mark; Rokosz, Maciej K.; Weaver, Paul M.; Gregg, John M.; Viola, Giuseppe; Cain, Markys G; Brennecka, G. L
<x xml:space="preserve">Abstract</x> In this work, we demonstrate a very high‐energy density and high‐temperature stability capacitor based on SrTiO3‐substituted BiFeO3 thin films. An energy density of 18.6 J/cm3 at 972 kV/cm is reported. The temperature coefficient of capacitance (TCC) was below 11% from room temperature up to 200°C. These results are of practical importance, because it puts forward a promising novel and environmentally friendly, lead‐free material, for high‐temperature applications in power electronics up to 200°C. Applications include capacitors for low carbon vehicles, renewable energy technologies, integrated circuits, and for the high‐temperature aerospace sector.